FINDINGS OF GLYCAEMIC CONTROL AND OTHER PARAMETERS AFTER INSULIN DEINTENSIFICATION EXERCISE AMID INSULIN SUPPLY INADEQUACY IN A TERTIARY CARE CENTRE - Amin, Md Syazwan Md (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Our country has recently experienced a period of human insulin supply challenges which prompted different centres all over the country to come up with plans to reduce insulin usage while avoiding diabetes management failure. An assessment after adhering to this plan is necessary to decide the efficacy and safety of such actions. METHODOLOGY We reviewed the records of patients with Type 2 Diabetes Mellitus managed under the diabetes clinic Hospital Tengku Ampuan Afzan, Kuantan from July 2024 to November 2024. These patients underwent insulin deintensification based on the Pahang insulin deintensification guideline 2024. Their weight, fasting blood sugar (FBS), HbA1c and total daily insulin dose were recorded at baseline and subsequent follow-up. Data were compared and analysed using Microsoft Excel 2024 and IBM SPSS Statistics Data Editor Version 23. RESULT Nine patients were included. They had a median diabetes duration of 12 (1–21) years. Mean HbA1c was 9.6 (±2.6)% and median total daily insulin dose (TDD) was 28 (10–86) units. After a median follow-up duration of 4 (3–9) months, there was an improvement in mean HbA1c to 8.6 (±1.6)% while TDD dropped by 42.8%. There was no improvement in FBS. Patients' weight also dropped by 4%. None of the patients were admitted for diabetic ketoacidosis but two of them had episodes of mild hypoglycaemia after initiation of sulphonylureas. CONCLUSION While insulin remains the most potent treatment in resolving hyperglycaemia in Type 2 DM, in some patients, there is always a risk of over-insulinisation which may sometimes impair their supply. Despite being limited due to small sample size and short duration of follow-up, these findings provide a glimpse into the potential benefits in glycaemic control by optimising use of oral glucose lowering drugs subsequently reducing the reliance on insulin. However, cautious use of sulphonylurea is vital as some patients may still have normal insulin reserves.